Activity of LpxC inhibitors on carbapenemase-producing Citrobacter spp. clinical isolates - Víctor Vinuesa; Raquel Cruces; Javier E. Cañada-García; Jesús Oteo-Iglesias; Andrés Corral-Lugo; Michael J. McConnell (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objective: Citrobacter spp. are commonly found in the human intestine and can cause antibiotic-resistant infections. Inhibitors of LpxC, an enzyme involved in the synthesis of lipid A, have demonstrated potent activity against multiple Gram-negative species, but their activity in Citrobacter spp. has not been well-characterised. The objective of the present study was to evaluate the antimicrobial activity of LpxC inhibitors against carbapenemase-producing Citrobacter spp. clinical isolates. Methods: The MICs of LpxC-2, LpxC-4, and CHIR-090 LpxC inhibitors were determined for 61 clinical isolates with high genetic diversity. Time-kill assays with the three LpxC inhibitors were performed with two Citrobacter spp. strains, with low (Cit 52) and high (Cit 110) LpxC inhibitor MIC values. Results: LpxC-4 was shown to be the most potent inhibitor (MIC90 = 0.5 mg/L). In general, the three LpxC inhibitors demonstrated similar activity between Citrobacter spp. isolates harbouring type A (n = 11 isolates), B (n = 39 isolates), and D (n = 11 isolates) carbapenemases. All LpxC inhibitors showed bactericidal activity at concentrations 4× the MIC and no activity at ¼× the MIC at 24 h for the two Citrobacter spp. strains analysed. Conclusions: Although LpxC-4 had a lower MIC90 value compared with CHIR-090, CHIR-090 showed a bactericidal effect at short times and prevented the regrowth of both isolates in the time-kill assays. In terms of cross-resistance, all three structurally similar LpxC inhibitors showed a moderate positive correlation between their activity.